Dietary-Nutraceutical Properties of Oat Protein and Peptides - Rafique, Hamad; Dong, Rui; Wang, Xiaolong; Alim, Aamina; Aadil, Rana Muhammad; Li, Lu; Zou, Liang; Hu, Xinzhong (Frontiers in Nutrition, 2022)
Oats are considered the healthiest grain due to their high content of phytochemicals, dietary fibers and protein. In recent years, oat protein and peptides have gained popularity as possible therapeutic or nutraceutical candidates. Generally, oat peptides with bioactive properties can be obtained by enzymatic hydrolysis of protein, and are known to have a variety of regulatory functions. This review article focused on the nutraceutical worth of oat protein and peptides, and also describes the application of oat protein as functional ingredient. Outcomes of this study indicated that oat protein and peptides present various therapeutical properties including antidiabetic, antioxidant, antihypoxic, antihypertensive, antithrombotic, antifatigue, immunomodulatory and hypocholestrolaemic. However, most of conducted studies are limited to in vitro conditions, so far, fewer data available on assessing the effectiveness of oat peptides in vivo. Future effort should direct at performing systematic animal studies, in addition, clinical trials also need to be conducted to fully support the development of functional food products, nutraceutical and therapeutical applications.